Work - Legendre, Camille (The Canadian Encyclopedia (TCE), 2006)
At different times in different cultures, work has been considered a divine punishment, an activity unworthy of free citizens, as the best possible way to accomplish the will of the Creator, or as the best possible way to earn a living. In modern Canadian society, work has been for most people the central activity around which life has revolved. However in the last decades, major technological, economic, social and cultural changes have raised a good deal of questioning about its future. "Work" may be on the threshold of a new era....